1999
DOI: 10.1007/s007050050519
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and interviral relationships of a flexuous filamentous virus causing mosaic disease of sugarcane (Saccharum officinarum L.) in India

Abstract: A virus isolate causing mosaic disease of commercial sugarcane was purified to homogeneity. Electron microscopy revealed flexuous filamentous virus particles of ca 890 x 15 nm. The virus isolate reacted positively with heterologous antiserum to narcissus latent virus form UK, but failed to react with potyvirus group specific antiserum. N-terminal sequencing of the intact coat protein (CP) and the tryptic peptides indicated that the virus was probably a potyvirus but distinct from several reported potyviruses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 15 publications
2
35
1
2
Order By: Relevance
“…1a), and PS 864 variety was predominantly affected with from 1 to 62% of the plants having symptoms. SCSMV, a virus that causes streak mosaic of sugarcane, was first reported by Hall et al (1998) and has been found in Pakistan, India, Bangladesh, Sri-Lanka, Vietnam and Thailand (Chatenet et al 2005;Hema et al 1999). Based on phylogenetic analyses, Rabenstein et al (2002) and Hema et al (2002) considered that SCSMV is not in the genus Tritimovirus, but should be placed in a new genus in Potyviridae.…”
mentioning
confidence: 95%
“…1a), and PS 864 variety was predominantly affected with from 1 to 62% of the plants having symptoms. SCSMV, a virus that causes streak mosaic of sugarcane, was first reported by Hall et al (1998) and has been found in Pakistan, India, Bangladesh, Sri-Lanka, Vietnam and Thailand (Chatenet et al 2005;Hema et al 1999). Based on phylogenetic analyses, Rabenstein et al (2002) and Hema et al (2002) considered that SCSMV is not in the genus Tritimovirus, but should be placed in a new genus in Potyviridae.…”
mentioning
confidence: 95%
“…In India, SCSMV was first reported during 1999 [9], and since then, it is reported to have spread into different geographical locations, limiting sugarcane production [10,11]. Earlier reports on the genetic diversity of SCSMV based on coat protein (CP) gene sequences revealed the existence of high levels of genetic variation among Indian SCSMV isolates [11], and the isolates were differentiated into three clusters.…”
mentioning
confidence: 98%
“…Recently, Balarabe et al (2014) mentioned that the Johnsongrass mosaic virus (JGMV) and the Maize dwarf mosaic virus (MDMV) cause mosaic disease in sugarcane in Nigeria. To this day, the presence of the SrMV has been confirmed in the United States, China, and Vietnam (Yang and Mirkov, 1997;Grisham and Pan, 2007;Ha et al, 2008;Zhang et al, 2016), whereas SCSMV is limited to the sugarcane producing areas of the Asian continent (Hall et al, 1998;Hema et al, 1999;Rao et al, 2006). However, due to the proximity of Mexico to the United States, it is likely that SrMV is infecting sugarcane plants in our country.…”
Section: Discussionmentioning
confidence: 90%
“…(Grisham, 1994;Xie et al, 2009), o incluso aquellas muestras con mosaicos severos y positivas al SCMV contengan infecciones virales mixtas. Recientemente Balarabe et al (2014) , 1997;Grisham y Pan, 2007;Ha et al, 2008;Zhang et al, 2016), mientras que el SCSMV está limitado para las zonas cañeras del continente asiático (Hall et al, 1998;Hema et al, 1999;Rao et al, 2006). Sin embargo, debido a la cercanía de Estados Unidos con México sería muy probable que el SrMV se encuentre infectando a las plantas de caña de azúcar en nuestro país.…”
Section: Discussionunclassified